2009
DOI: 10.1007/s12517-009-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

التعامل مع التعقيدات الزلزالية باستخدام التقنيات الحاسوبية العصبية وتحديد قدرها الزلزالي ببعض المتوقعات منخفضة المقارنة

Abstract: Earthquake, being one of the most hazardous geophysical events, has fascinated the scientists all over the globe to investigate an efficient predictive methodology. In India, earthquake is not a rare event. Purpose of the present paper is to view the earthquake as a complex system and then to estimate the magnitude of earthquake over Indian subcontinent using artificial neural network with backpropagation learning. The day, month, and year of occurrence of the earthquake, latitude of the place, and the longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Relevance of the said predictors in prediction of TO time series in daily scale has been discussed thoroughly in Chattopadhyay and Chattopadhyay (2009a). The correlation matrices for the said variables are found to be the following:…”
Section: Implementation Procedures and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relevance of the said predictors in prediction of TO time series in daily scale has been discussed thoroughly in Chattopadhyay and Chattopadhyay (2009a). The correlation matrices for the said variables are found to be the following:…”
Section: Implementation Procedures and Discussionmentioning
confidence: 99%
“…In the hidden layer, we have taken four nodes and for this number of hidden nodes the ANN remains free from the problem of over parameterization. To avoid the asymptotic effect, the data are standardized to [0,1] as follows (Chattopadhyay and Chattopadhyay 2009a):…”
Section: Implementation Procedures and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was tested within different years with wide time and location perspective. Chattopadhyays [10] predicted the magnitude of earthquake over Indian subcontinent benefitting artificial neural network with backpropagation learning. ANN model established by Gul and Guneri [11] for the earthquake casualty estimation, which takes into account earthquake time, earthquake magnitude, and population frequency as the parameters for training network in Turkey from 1975.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another hazardous area, India, has been subjected to study by means of ANN's [9]. After evaluating several architectures, the authors concluded that the best one must include two hidden layers and the sigmoid transfer function.…”
Section: Related Workmentioning
confidence: 99%